Efficient charge carrier separation and excellent visible light photoresponse in Cu2O nanowires. (August 2018) - Zhou, Tingwei; Zang, Zhigang; Wei, Jing; Zheng, Junfeng; Hao, Jiongyue; Ling, Faling; Tang, Xiaosheng; Fang, Liang; Zhou, Miao
Abstract: Last decade has witnessed a surge of research pertaining to Cu2 O nanowires for fields of photocatalysts, sensors, solar cells and rechargeable battery systems owing to their unique physicochemical properties. Their atomic properties, especially the size dependent electronic structures, however, remain unknown. Herein, by combining systematic first-principles calculations with material synthesis, characterization, device fabrication and measurement, we investigated physical properties of Cu2 O nanowires and their applications in visible light photodiodes. We explored Cu2 O nanowires with triangular and hexagonal cross sections of a series of diameter size, and found that they have favorable formation energies, indicative of facile synthesis. These nanowires have tunable direct band gap ranging from 2.2 to 5.4 eV, and a simple model is derived to effectively predict gap size. Remarkably, obvious spatially separated charge distribution of conduction and valance band edges was observed, ensuring long lifetime of excited electron-hole pairs that may greatly benefit performance of optoelectronic devices. Experimentally, we synthesized well-crystallized Cu2 O nanowires and fabricated photodiodes, which exhibit a fast rise time of 9.86 ms, decay time of 27.37 ms, and high responsivity of 10 A/W. We expect these results to shed new light on Cu2 O nanostructures for scalable, versatile and high-performance optoelectronic devices. Graphical abstract: The atomic electronic structures of Cu2 O nanowires were investigated by combining systematic first-principles calculations with material synthesis, characterization, device fabrication and performance measurements. These nanowires exhibit tunable band gap, efficient carrier separation, and excellent visible light photoresponse. fx1 Highlights: For the first time, Cu2 O nanowires of different size have been systematically investigated by first-principles calculations. Cu2 O nanowires have favorable formation energies, and exhibit direct band gap with tunable gap size ranging from 2.2 to 5.4 eV. Obvious spatially separated charge distribution of VBM/CBM is observed, ensuring long lifetime of excited electron-hole pairs. High-performance photodiodes based on Cu2 O nanowires were fabricated, which exhibit very high responsivity.